ICT: creation of avatars to integrate skills in an EFL classroom - Ulloa Moscoso, Adriana; Ureña Gallegos, Tania
This project is about the integration of skills through the use of Avatars, specifically through the use of Vokis within an EFL class. The work contains three main parts, divided into five chapters: The first part analyzes the problems and situations that led to propose new technological resources such as avatars as possible solutions. Moreover, this part refers to the reasons which justify this work and the objectives to be reached. The second part introduces the development of the theoretical framework that supports the theme. Topics such as the new roles in education, advantages and disadvantages of educating with technology, and the term educational technology itself, are all involved with the basic concept of ICT in education as the starting point. The last part, educational technology, leads to technological resources where Avatar and Voki categories originate. To conclude, since our topic is focused on technological activities based on drills and repetition to work with language skills, topics such as the integration of skills and Behaviorism are also dealt with. Finally, the third part establishes the practical part of this investigation. It is focused on the elaboration of lesson plans based on the integration of skills achieved by the aid of Vokis, as well as the results and recommendations evoked from this application.